Copper‐Mediated Reversible Deactivation Radical Polymerization in Aqueous Media. Issue 33 (16th July 2018) - Jones, Glen R.; Anastasaki, Athina; Whitfield, Richard; Engelis, Nikolaos; Liarou, Evelina; Haddleton, David M.
Abstract: Key advances within the past 10 years have transformed copper‐mediated radical polymerization from a technique which was not very tolerant of protic media into a range of closely related processes capable of controlling the polymerization of a wide range of monomers in pure water at ppm catalyst loadings. This approach has afforded water‐soluble macromolecules of desired molecular weight, architecture, and chemical functionality, with applications ranging from drug delivery to oil processing. In this Review we highlight and critically evaluate the synthetic methods that have been developed to control radical polymerization in water by using copper complexes as well as identify future areas of interest and challenges still to be overcome. Abstract : Water features : Copper‐mediated radical polymerization was originally not very tolerant of protic media, but variants are now available for the polymerization of assorted monomers in pure aqueous media. Water‐soluble macromolecules can be obtained with the desired molecular weight, architecture, and chemical functionality.